Hazarat Yaqub (AS) - Karam , Ambia (Lahore ' Karachi Children's publication)
rophet Yaqub (pbuh) was born in Palestine, and was the son of Prophet Ishaq (pbuh). He is known for leading his life in the footsteps of his father and grandfather, spreading the message of the Oneness of God, and advising followers to pray and give in charity.